Registration of Marriage as Fulfillment of Marriage Requirements According to Islamic Principles - Arifuddin, Qadriani (Nurani, 2024)
Marriage registration plays a central role in regulating marital relations and has a significant impact on the rights and obligations of married couples. However, there are still those who view marriage registration as merely a state document without a clear textual basis, leading to the prevalence of unregistered marriages in Indonesia. This research aims to analyze the urgency and implications of marriage registration in the context of Islamic law. The research adopts a library-based approach. The findings indicate that marriage registration under Islamic law carries significant implications. Apart from providing legal validity to the husband and wife bond, marriage registration also plays an important role in protecting the marital rights of each individual, including inheritance rights, maintenance and other rights. It was found that marriage registration not only prevents potential future disputes through clarifying marital status, but can also be considered as fulfilling the conditions for marriage in accordance with Islamic principles. Furthermore, the confirms that marriage registration makes a positive contribution to social order in Islamic society, makes it easier to regulate and monitor marital relations and maintain morality and ethics in family institutions. Therefore, this research supports the importance of marriage registration within the framework of Islamic law as a solid foundation for maintaining justice, order and prosperity within marriage.